A study on ovine tick-borne hemoprotozoan parasites (Theileria and Babesia) in the East Black Sea Region of Turkey - Altay, Kursat; Dumanli, Nazir; Aktas, Munir (Springer, 2012)
In this study, the frequency of Theileria and Babesia species was assessed via reverse line blotting and blood smear-based diagnostic methods in small ruminants. A total of 201 apparently healthy animals from 26 randomly selected herds located in 4 locations (Artvin, Giresun, Gumushane, and Tokat) of East Black Sea Region of Turkey were investigated for the blood protozoans. In a polymerase chain reaction (PCR), the hypervariable V4 region of the 18S ribosomal RNA gene was amplified with a set of general primers specific for all Theileria and Babesia species. The PCR products were hybridized against catchall and species-specific (Theileria spp., Theileria lestoquardi, Theileria ovis, Theileria sp. OT1, Theileria sp., OT3, Theileria sp., MK, Theileria luwenshuni, Theileria uilenbergi, Babesia spp., Babesia ovis, Babesia motasi, and Babesia crassa) probes. Theileria piroplasms were identified in nine (4.47%) samples by microscopic examination. Reverse line blotting (RLB) detected the infection in 19.90% of the samples. The infection rate of sheep (28.90%) was higher than goats (4.10%). T. ovis, Theileria sp., MK, and Theileria sp. OT3 were detected by RLB. The most prevalent Theileria species was T. ovis (18.90%) followed by Theileria sp. MK (0.99%). Theileria sp. OT3 was detected in one sample (0.43%). A single animal was infected as mix with T. ovis and Theileria sp. MK. The other Theileria (T. lestoquardi, Theileria sp. OT1, T. luwenshuni, and T. uilenbergi) and Babesia (B. ovis, B. motasi, and B. crassa) species were not detected. This study is the first molecular survey on ovine tick-borne protozoans in East Black Sea Region of Turkey.
Keywords: Small Ruminants; Genetic Diversity; Identification; Sheep; Pcr; Differentiation; Prevalence; Infection; Diagnosis